Restare, intraprendere, tornare - Mutti, Valentina; Ferro, Anna (Antropologia Pubblica, 2021)
The paper investigates the nature of transnational relations of Burkinabé youth in Italy. By focusing on remittances, investments and plans for the future, the study shows the heterogeneity of second generation members due to age of arrival, educational paths and job inclusion outcomes. Transnational ties seem to be strong for almost everyone as well as the will to contribute to Burkina Faso development, but the behaviors might be quite diverse. Some Burkinabé youth with higher education tend to send home little amounts of money, often mediated by their parents; other young workers support friends' or relatives' small businesses and local activities with the aim of obtaining a small individual profit, while others already married support their left behind families. Moreover, Burkinabé youth experiences more uncertainty compared with first generation due to economic crisis and the today challenges to imagine their future: this implies hesitation on investing or find more opportunities in Italy, Burkina Faso or a third country. Different from the activism in first generation migrants and/or ethnic Associations, youth play a role in imagining support activities and social help to Burkina Faso, by navigating among innovations, ambiguities and skills transfer.